Usability guidelines for elderly website interface - Rasyiqah Rusdi; Noraidah Sahari@Ashaari; Siti Fadzilah Mat Noor (Penerbit Universiti Kebangsaan Malaysia, 2017)
The elderly population is growing every year. Most of them are retirees. The number of elderly are significantly increasing in the near future. Therefore, it is important to see them as a large scale users of technology. However, the information system that exists is mostly general and not specific to a particular group. For the elderly, this is a constraint for those who have certain deficiencies such as having reduced visibility, movement, and deterioration of cognitive skills. It is essential to conduct a study to identify the problems faced by the elderly in using existing information system. Therefore, the objective of this paper is to discuss the construction of a usability guideline for elderly website interface. The study began by identifying the problems faced by the elderly to the usability of the current information systems that are available interviews. Usability characteristics of information systems that are suitable to the elderly are identified and a guideline for the elderly interface usability of information systems is constructed. These guideline illustrates that a friendly website interface for elderly are sites that provide usage facilities to the elderly such as simple language, large font size, navigation that is easy to use and has a combination of media such as video and audio. These guidelines are used to develop usability’s website interface for elderly. The website evaluation is conducted to assess the usability features used in the design. The website is tested by target users. Feedback from the elderly is used to enhance the interface to become more usable and can serve as a reference for web developers.